1997
DOI: 10.1097/00005373-199709000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Value of Thoracic Computed Tomography in the First Assessment of Severely Injured Patients with Blunt Chest Trauma

Abstract: TCT is highly sensitive in detecting thoracic injuries after blunt chest trauma and is superior to routine CXR in visualzing lung contusions, pneumothorax, and hemothorax. Early TCT influences therapeutic management in a significant number of patients. We therefore recommend TCT in the initial diagnostic work-up of patients with multiple injuries and with suspected chest trauma because early and exact diagnosis of all thoracic injuries along with sufficient therapeutic consequences may reduce complications and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
161
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(181 citation statements)
references
References 36 publications
9
161
1
10
Order By: Relevance
“…A report [11] advocated that TCT may be helpful in the treatment of hemodynamically stable patients with blunt chest trauma. On the contrary, others [6,12,13] suggested that TCT should be withheld in the initial management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A report [11] advocated that TCT may be helpful in the treatment of hemodynamically stable patients with blunt chest trauma. On the contrary, others [6,12,13] suggested that TCT should be withheld in the initial management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and consequent specific interventions are fundamental issues in traumatic injury of the lung (14). CT scan plays a key role in the management of chest trauma and it has a considerable impact on the following therapeutic decisions (14).…”
Section: Discussionmentioning
confidence: 99%
“…CT scan plays a key role in the management of chest trauma and it has a considerable impact on the following therapeutic decisions (14). The introduction in the clinical practice of multidetector CT allows rapid and complete definition of all lesions in polytrauma patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…CT scans form the mainstay of diagnosis and evaluation unlike Chest Radiographs. 4 Though technically less morbid, management by endovascular stents is not ideally suited for most thoracic aortic injuries. 5 Surgery remains the mainstay of any possible salvage, but perfusion, metabolism, and oxygen delivery to the spinal cord during the vulnerable period of aortic occlusion is crucial.…”
Section: Discussionmentioning
confidence: 99%